2001
DOI: 10.1046/j.1432-1327.2001.02333.x
|View full text |Cite
|
Sign up to set email alerts
|

The hemoglobin system of the brown moray Gymnothorax unicolor

Abstract: The Gymnothorax unicolor hemoglobin system is characterized by two components, called cathodic and anodic on the basis of their isoelectric point, which were separated by ion-exchange chromatography. The oxygen-binding properties of the purified components were studied in the absence and presence of chloride and/or GTP or ATP in the pH range 6.5-8.0. Stripped cathodic hemoglobin showed a small reverse Bohr effect, high oxygen affinity, and low co-operativity; the addition of chloride only caused a small decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…[21][22][23] It seems that GTP can bind and change the secondary and tertiary structures of hemoglobin. We showed that reason of the decreased affinity of hemoglobin for oxygen, as stated by Tamburrini et al, 11 may be because of the changed secondary and tertiary structures of hemoglobin. Our data suggest that GTP acts as a regulator of hemoglobin's affinity for oxygen by structural changes in the protein.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…[21][22][23] It seems that GTP can bind and change the secondary and tertiary structures of hemoglobin. We showed that reason of the decreased affinity of hemoglobin for oxygen, as stated by Tamburrini et al, 11 may be because of the changed secondary and tertiary structures of hemoglobin. Our data suggest that GTP acts as a regulator of hemoglobin's affinity for oxygen by structural changes in the protein.…”
Section: Resultssupporting
confidence: 64%
“…Tamburrini et al have reported that the affinity of hemoglobin, for oxygen, was reduced dramatically in the present of GTP. 11 However, there are still unanswered questions like: how GTP affects the hemoglobin structure?…”
Section: Introductionmentioning
confidence: 99%
“…parasitica typifies class II fish, having cathodic Hb with relatively high O2 affinity, a slight, reversed Bohr effect in the absence of organic phosphate and a large effect of ATP (that normalizes the Bohr effect) as well as an anodic Hb with relatively low affinity and marked Bohr and ATP effects -as found in other anguillids (Weber et al, 1976a;Fago et al, 1995;Tamburrini et al, 2001) and catfish Powers and Edmundson, 1972;Weber et al, 2000;Fig.·8). Unexpectedly, the affinities of stripped S. parasitica Hbs [P50=14·Torr (1.89·kPa) and 33·Torr (4.4·kPa) for Hb I and II, respectively, at pH 7.2 and 25°C] are low compared with those obtained by the same technique in eel and catfish cathodic and anodic Hbs [P50=≈2·Torr (0.23·kPa) and ≈8.5·Torr (1.13·kPa), respectively; Weber et al, 1976a;Fago et al, 1995Fago et al, , 1997bWeber, 2000a] but are similar to those in trout Hbs [P50=~17-20·Torr (2.27-2.67·kPa) at 20°C; Weber et al, 1976b] -all of these species are classified as class II.…”
Section: Isohb Differentiationmentioning
confidence: 93%
“…In another study, Ling reported a decrease in the Sr/Ca ratios in the otoliths of Gymnothorax reticularis during metamorphosis (Ling et al, 2005). In addition, Tamburrini et al (2001) studied the structure/function relationships of the brown moray (Gymnothorax unicolor) hemoglobin system. However, there is still debate on the number of Gymnothorax species that inhabit the South and East China Seas.…”
Section: Introductionmentioning
confidence: 99%